2023
DOI: 10.3390/foods12132545
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Comprehensive Quality Evaluation System for Foxtail Millet from Different Ecological Regions

Abstract: Foxtail millet (Setaria italica L.) is a critical grain with high nutritional value and the potential for increased production in arid and semiarid regions. The foxtail millet value chain can be upgraded only by ensuring its comprehensive quality. Thus, samples were collected from different production areas in Shanxi province, China, and compared in terms of quality traits. We established a quality evaluation system utilizing multivariate statistical analysis. The results showed that the appearance, nutritiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 41 publications
0
0
0
Order By: Relevance
“…Previous research showed that the nutritional quality of rice [35], wheat [36], maize [37], foxtail millet [27,28], etc., was significantly different in different production areas. Our study also reached a similar conclusion; we found the contents of grain fillings in the foxtail millet, such as crude fat, amylose, and amylopectin, significantly varied in different areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research showed that the nutritional quality of rice [35], wheat [36], maize [37], foxtail millet [27,28], etc., was significantly different in different production areas. Our study also reached a similar conclusion; we found the contents of grain fillings in the foxtail millet, such as crude fat, amylose, and amylopectin, significantly varied in different areas.…”
Section: Discussionmentioning
confidence: 99%
“…According to Zhang et al [27], there were significant differences in the grain color, nutritional content, and culinary value of foxtail millet grown in various ecological areas. Ning et al [28] found that altitude and precipitation showed a significant positive effect on the grain quality of foxtail millet, whereas a ≥20 • C accumulated temperature exhibited a significant negative impact.…”
Section: Introductionmentioning
confidence: 99%